Coupling clinical exome sequencing with functional characterization studies to diagnose a patient with familial Mediterranean fever and MED13L haploinsufficiency syndromes. Issue 6 (18th April 2017) - Mullegama, Sureni V.; Jensik, Phillip; Li, Chen; Dorrani, Naghmeh; ,; Kantarci, Sibel; Blumberg, Bruce; Grody, Wayne W.; Strom, Samuel P.
Key Clinical Message: Clinicians should consider that clinical exome sequencing provides the unique potential to disentangle complex phenotypes into multiple genetic etiologies. Further, functional studies on variants of uncertain significance are necessary to arrive at an accurate diagnosis for the patient. Abstract : Clinicians should consider that clinical exome sequencing provides the unique potential to disentangle complex phenotypes into multiple genetic etiologies. Further, functional studies on variants of uncertain significance are necessary to arrive at an accurate diagnosis for the patient.